Motor cortico-nigral and cortico-entopeduncular information transmission and its modulation by buspirone in control and after dopaminergic denervation - Vegas-Suárez, Sergio; Morera-Herreras, Teresa; Requejo, Catalina; Lafuente, José Vicente; Moratalla, Rosario; Miguélez, Cristina; Ugedo, Luisa (Frontiers in Pharmacology, 2022)
Cortical information is transferred to the substantia nigra pars reticulata (SNr) and the entopeduncular nucleus (EP), the output structures of the basal ganglia (BG), through three different pathways: the hyperdirect trans-subthalamic and the direct and indirect trans-striatal pathways. The nigrostriatal dopamine (DA) and the activation of 5-HT1A receptors, distributed all along BG, may modulate cortical information transmission. We aimed to investigate the effect of buspirone (5-HT1A receptor partial agonist) and WAY-100635 (5-HT1A receptor antagonist) on cortico-nigral and cortico-entopeduncular transmission in normal and DA loss conditions. Herein, simultaneous electrical stimulation of the motor cortex and single-unit extracellular recordings of SNr or EP neurons were conducted in urethane-anaesthetised sham and 6-hydroxydopamine (6-OHDA)-lesioned rats before and after drug administrations. Motor cortex stimulation evoked monophasic, biphasic, or triphasic responses combination of an early excitation, an inhibition, and a late excitation in both the SNr and EP while an altered pattern of evoked response was observed in the SNr after 6-OHDA lesion. Systemic buspirone potentiated the direct cortico-SNr and cortico-EP transmission in sham animals since increased duration of the inhibitory response was observed. In DA denervated animals, buspirone administration enhanced early excitation amplitude in the cortico-SNr transmission. In both cases, the observed effects were mediated via 5-HT1A-dependent mechanism as WAY-100635 administration blocked buspirone’s effect. These findings suggest that in control condition, buspirone potentiates direct pathway transmission and DA loss modulates responses related to the hyperdirect pathway. Overall, the results may contribute to understand the role of 5-HT1A receptors and DA in motor cortico-BG circuitry functionality.